Organizational Justice, Work Discipline, and Employee Performance: A Literature Review - Diposentono, Ligan; Rivai Zainal, Veithzal; Hakim, Azis (International Journal of Advanced Multidisciplinary, 2023)
The aim of this paper is to provide a structured literature review on the constructs of organizational justice, work discipline, employee performance, and empirical evidence on the relationship between organizational justice, work discipline, and employee performance in Indonesia context of Indonesia. 25 (twenty five) papers published during 2018-2022 that investigates organizational justice, work discipline, employee performance, and empirical evidence on the relationship between organizational justice, work discipline, and employee performance were reviewed. The results of the literature review regarding the effect of the organizational justice on employee performance show different results. The majority (66,67%) indicated that the organizational justice has a positive and significant effect on employee performance, while the remaining (33,33%) indicated that the organizational justice has insignificant effect on employee performance. The effect of work discipline on employee performance also shows different results. The majority (76,92%) indicated that work discipline has a significant effect on employee performance and the remaining (23.08%) indicated that work discipline has insignificant effect on employee performance.